The preparation and characterization of hydrophilic macroporous foams from water soluble polymers grafted ultra‐high molecular weight polyethylene - Aydinli, Bahattin; Tincer, Teoman (Wiley, 2012)
AbstractMacroporous foams of water soluble polymers grafted ultra‐high molecular weight polyethylene (UHMWPE) were obtained by precipitation of hot xylene gel solutions in ethyl alcohol. The water soluble monomers used for grafting were acrylic acid (AA), methacrylic acid (MAA), acrylamide (AAm), N‐vinylpyrrolidone (NVP), and N‐N‐di‐methyl acrylamide (NNDAm). The morphology of the foams was investigated using the scanning electron microscope (SEM). Significant changes in the morphology and pore size were observed among the foams depending upon the type of grafting water soluble polymers. The porosity of the foams was uniform and varied from 1 to 10 μm. The percentages of the free volume and water uptake of the foams were measured. The foams obtained from grafted UHMWPE had an appreciable water uptake capacity and water could pass through them compared with the water repelling pure UHMWPE foams. The poly(NNDAm)‐grafted UHMWPE yielded markedly better foams than the others. The water soluble polymer‐grafted conventional polymers posses the characteristics of hybrid material where hydrophobic and mechanically strong UHMWPE make up a strong backbone and hydrophilic hydrogel affords biocompatibility. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013